OOP-ESEEM Spectroscopy: Accuracies of Distances of Spin-Correlated Radical Pairs in Biomolecules - Al Said, Tarek; Weber, Stefan; Schleicher, Erik (Frontiers in Molecular Biosciences, 2022)
Besides the commonly used electron–electron double resonance (ELDOR) technique, there are several other electron paramagnetic resonance (EPR) methods by which structure information can be obtained by exploiting the dipolar coupling between two radicals based on its characteristic r–3 dependence. In this contribution we explore the potential of out-of-phase-electron-spin echo envelope modulation (OOP-ESEEM) spectroscopy to collect accurate distance information in photo-sensitive (bio)molecules. Although the method has already been applied to spin-correlated radical pairs in several classes of light-active proteins, the accuracy of the information obtained has not yet been extensively evaluated. To do this in a system-independent fashion, OOP-ESEEM time traces simulated with different values of the dipolar and exchange couplings were generated and analyzed in the best-possible way. Excellent agreement between calculated and numerically fitted values over a wide range of distances (between 15 and 45 Å) was obtained. Furthermore, the limitations of the method and the dependence on various experimental parameters could be evaluated.